Information System for Rapid Assessment of Emergency Responses Based on Android Applications for BPBD of Aceh Barat - Kusuma, Muchtar; Nizamuddin, Nizamuddin; Nasaruddin, Nasaruddin (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2020)
Rapid assessment is part of disaster emergency response that are covering quick and precise assessments to the calamity place, casualties and damaged building. So far, rapid assessment in BPBD Aceh Barat is still conducted manually without an information system within its management of disaster emergency response. To support a successful result in emergency response activity, designing an android based rapid assessment application system is demanded to facilitate the public users (community/volunteer) and trained users (TRC Team) of BPBD Aceh Barat. Research methods of the study was based on Perka BNPB and previous studies. Then, continued by building prototype, and users System Usability Scale test. This research result is an android based rapid assessment application. The procedure is by inputting data by user via Android application that contained disaster info, casualties, refugee data, building damage, volunteer and humanitarian logistic. Then validated at www.tdb-aceh.com. Users can access to news and information, BNPB regulations, important dials, and TRC BPBD members on application. SUS test results showed that public users of 12 respondents average score is 68,95 and trained users of 3 respondents average score is 67,5. Analysis to both respondents group showed that the application is well-integrated, user friendly, and easy to understand.